Integrated In Silico Approach Discovery of β-Caryophyllene from Piper crocatum Ruiz & Pav. as an Antidiabetic Candidate: β-Caryophyllene from Piper crocatum Ruiz & Pav. as an Antidiabetic Candidate - Febyaningrum, Vitasigi Dwi; Putri Kharisma Novita Sari; Hadi , Saptono (Journal of Tropical Life Science, 2026)
Type 2 diabetes mellitus (T2DM) remains a significant global health challenge, responsible for more than 90% of all diagnosed diabetes cases worldwide. The progression of T2DM is primarily driven by insulin resistance and progressive pancreatic β-cell dysfunction, both of which contribute to various metabolic complications. Metformin is widely used as a first-line antidiabetic drug. However, its long-term use is associated with gastrointestinal disturbances, lactic acidosis, and vitamin B12 deficiency. These limitations highlight the need for safer and more effective therapeutic alternatives. β-caryophyllene, a sesquiterpene compound derived from the stem extract of Piper crocatum Ruiz & Pav., has demonstrated antioxidant, anti-inflammatory, and antilipidemic properties that may support its potential as an antidiabetic agent. This study evaluated the pharmacological potential of β-caryophyllene as an antidiabetic agent through an in silico approach. The analysis included drug-likeness assessment via Lipinski’s Rule of Five, ADMET profiles, network pharmacology, such as KEGG pathway and GO, inhibitory activity prediction using SVM regression in DataWarrior, and molecular docking through AutoDockTools and BIOVIA Discovery Studio, with metformin used as a reference standard. β-caryophyllene fully complies with Lipinski’s Rule of Five, indicating good drug-likeness and potential for oral bioavailability. The IC50 prediction results indicated that β-caryophyllene exhibited stronger inhibitory potential than metformin against several key T2DM-related proteins, including IL6, HSP90AA1, NOS3, TLR4, KRAS, and NFKB1. Consistently, molecular docking analysis demonstrated that β-caryophyllene also had stronger interactions with these targets, exhibiting higher binding affinities compared to metformin. These proteins are implicated in insulin resistance, inflammation, and vascular dysfunction. Additionally, pharmacokinetic data demonstrated high intestinal absorption (94.8%), extensive distribution (VDss ≈ 4.49 L/kg), minimal CYP450 inhibition, and limited toxicity risks. Collectively, β-caryophyllene exhibits good pharmacological properties and multitarget activity, supporting its candidacy for further in vitro and in vivo studies as a potential therapeutic agent for T2DM.